MENGANGKAT BUDAYA PECINAN YANG MELEBUR SEBAGAI ATTRACTOR BARU YANG MENUNJANG KAWASAN DAN SEBAGAI IDENTITAS KAWASAN PASAR LAMA TANGERANG - Galant Giatica Eka Surya; Franky Liauw (Jurusan Arsitektur dan Perencanaan, 2023)
The Pasar Lama Tangerang Chinatown area is an area that became the forerunner to the formation of the City of Tangerang. Historic sites such as typical Chinatown buildings are evidence of the spread of the Confucian religion and Chinese settlements, the Jami' Kalipasir Mosque as the oldest mosque is evidence of the spread of Islam, and the Cisadane River as a transportation and trade route at its time. This area is also one of the Chinatown areas with the uniqueness that produced a new breed, the Benteng Chinese tribe (a fusion of Chinese, Betawi and Sudanese tribes). But unfortunately the local historical and cultural sites are now starting to disappear along with the times. This area is now better known as a traditional market and culinary center at night. The development of the area which is focused on traditional markets and culinary centers has resulted in a compaction of activities at one point which causes the surrounding points to become dead spaces and undeveloped. Now this area is very clearly seen as a market area and a culinary center, the uniqueness of the Chinatown village is starting to disappear with the typical Chinatown houses that are damaged, abandoned. The culinary center is driving a change in the area to become more modern as new, more modern eateries and retail emerge that take advantage of several Chinatown shophouses to be renovated as a modern design or cover the original building with a modern façade design. In dealing with these problems, local cultures that merge with each other are brought back which are interpreted in the form of activity programs so that the area has new activities that support existing activities. Utilization of dead areas due to lack of development is used as design points that accommodate new activities so that they are active as a whole. The goal is that each dot can be active and offer a variety of activities so as to create a space travel experience for visitors. The design of the cultural center and the rearrangement of the riverside area are used as the first step as a generator of regional development with the characteristics of local culture. Keywords: Chinatown culture; cultural centers; identity; regional rearrangement; supporting activities Abstrak Kawasan Pecinan Pasar Lama Tangerang merupakan daerah yang menjadi cikal bakal terbentuknya Kota Tangerang. Situs bersejarah seperti bangunan khas Pecinan menjadi bukti penyebaran agama Konghucu dan Pemukiman Tionghoa, Masjid Jami’ Kalipasir sebagai masjid tertua bukti dari penyebaran agama islam, dan Sungai Cisadane sebagai jalur transportasi dan perdagangan pada masanya. Kawasan ini juga merupakan salah satu daerah Pecinan dengan keunikannya yang menghasilkan peranakan baru, suku Cina Benteng (Peleburan suku Tionghoa, Betawi dan Sunda). Namun sayangnya situs sejarah dan kebudayaan setempat sekarang mulai hilang seiring dengan berkembangnya zaman. Kawasan ini sekarang lebih dikenal sebagai pasar tradisional dan pusat kuliner pada malam hari. Pengembangan kawasan yang terfokus pada pasar tradisional dan pusat kuliner menyebabkan terjadinya pemadatan aktivitas di satu titik yang menyebabkan titik-titik sekitarnya menjadi ruang mati dan tidak ikut berkembang. Sekarang ini kawasan sangat jelas terlihat sebagai daerah pasar dan pusat kuliner, kekhasannya akan kampung pecinan mulai hilang dengan rumah-rumah khas pecinan yang rusak, ditinggalkan, dan terbengkalai. Pusat kuliner mendorong perubahan kawasan yang lebih modern seiring munculnya tempat makan baru yang lebih modern yang memanfaatkan beberapa bangunan ruko khas pecinan yang direnovasi atau menutupi bangunan aslinya dengan desain fasad yang modern. Dalam menangani permasalahan tersebut, kebudayaan lokal yang saling melebur diangkat kembali yang diinterpretasikan dalam bentuk program aktivitas sehingga kawasan memiliki aktivitas baru yang mendukung atau menunjang aktivitas yang sudah ada. Pemanfaatan daerah-daerah yang mati karena kurang berkembang dijadikan sebagai titik-titik perancangan yang mewadahi aktivitas baru sehingga aktif secara menyeluruh. Tujuannya setiap titik-titik dapat aktif dan menawarkan variasi aktivitas sehingga menciptakan sebuah perjalanan pengalaman ruang untuk pengunjung. Perancangan pusat kebudayaan dan penataan ulang kawasan pinggiran sungai dijadikan langkah awal sebagai generator pengembangan kawasan dengan sifat-sifat kebudaan lokalnya.